Why do the Chinese make direct investment in the Europe? Insights from disaggregated bilateral data - Trung Nguyen, Thong; Vo, Xuan Vinh (Economics and Business Letters, 2021)
This study explores the economic factors of foreign direct investment (FDI) from China to Europe. By drawing data over 8 years and dataset from the International Monetary Fund (IMF) and World Bank (WB), we found that Chinese FDI outflows to Europe are driven by the recipient country’s fundamentals (trade openness, resource, institutional quality, and economic growth). These findings confirm the current literature while asserting counterintuitive facts. One of many points is that China is less likely to seek out the investment channel in the large economic status. More importantly, this study differs from extant literature by using the disaggregated panel data of bilateral FDI and trade openness. Therefore, our results would draw policy implications in terms of international finance.